Tata Cahaya Gedung Perpustakaan Umum Daerah Provinsi DKI Jakarta, Cikini, Menteng - Dwiky Dwiky Alvano (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
The library is one of the a important place to support the education that play as a role and serves to provide services to the society/users to obtain knowledge and information which is related to giving services to the society, so that it is needed to fulfill the convenience place for the users in the building of library, one of the aspect convenience that is needed is a convenience visual that is related to the system of the lighting that is work in it. The building of provincial library of DKI Jakarta used artifical lighting that is quite dominat in the evening activity, so that is why the energy that is needed it is quite large to run the activity. But in the exsiting utilization condition artifical lighting or in natural, this building can’t do good optimalize, that is caused by several thing, one of the is the space dimension that is large so the distribution of lighting is uneven, procedures for laying down artificial lighting that are not effective, and structuring furniture that blocks the entry of light Evaluation of the performance of artificial and natural lighting by changing the dimensions of openings, lighting layout, and furniture arrangement and optimizing the system of integration of natural and artificial lighting can support the visual comfort of space users in their activities.   Key words: library, lighting, convenience visual, activity.